Conjectural Variation Models and Supergames with Price Competition in a Differentiated Product Oligopoly - Michael Pfaffermayr (Austrian Institute of Economic Research (WIFO), 1999)
Conjectural variation models are popular in empirical research as they infer the degree of market power from real data. IO-theorists, however disapprove it for lack of theoretical foundation arguing that dynamic reactions are forced into a static model with the strategy space and time horizon only loosely defined. The presented model follows an idea put forward by Cabral (1995) and demonstrates that the CVmodel can be interpreted as the joint profit maximising steady state reduced form of a price setting supergame in a differentiated product market under optimal punishment strategies. For the symmetric-two firm case the CV-parameter is shown to cover the full range of possible outcomes - from Bertrand competition to joint unconstrained monopoly - depending on the degree of product differentiation, market growth, bankruptcy risk and the discount rate. For the asymmetric cost case numerical calculations are provided.
Keywords: L11; L13; D43; C73; 330; Conjectural variation models; supergames; product differentiation